Gender-Based Differences in Heart Failure Hospitalizations among Patients with Heart Failure Treated with Spironolactone - Mohammed A. Alshrahili, Hani Ahmed Abdelwahab, Ahmad Salawi, Yahya M. Fagihi, Hana M. Masmali, Mousa Q. Ghazwani, Ghala A. Khubrani, Sabreen T. Gammash, Maryam A. Awaji; Amnah S. Halawi, Meiaad A. Hendi, Samer S. Alshamrani, Ayil A.Sahli, Shahad A. Muhawish, Narjes A Shhar (Journal of International Crisis and Risk Communication Research, 2024)
Background: Gender-based variations in heart failure (HF) management and outcomes have been noted, especially in patients with reduced ejection fraction (HFrEF) treated with mineralocorticoid receptor antagonists (MRAs) like spironolactone. This study aimed to investigate gender-specific differences in HF-related hospitalizations among patients treated with spironolactone. Methods: In a prospective cohort, 509 ambulatory HFrEF patients (NYHA class II-IV) were enrolled and assessed over six months. Patients received spironolactone and were monitored for HF-related hospitalizations, all adverse events, and mortality. Results: After adjustment for potential covariates, the multivariate-adjusted regression analysis reveals that male gender was an independent predictor for HF hospitalization (hazard ratio (HR) = 1.972, 95% CI: 1.128–3.447, p = 0.017), a composite endpoint of mortality and morbidity (HR = 1.903, 95% CI: 1.127–3.214, p = 0.016), and all-cause hospitalization (HR = 4.955, 95% CI: 2.985–8.227, p < 0.001) but not all-cause mortality (HR = 0.672, 95% CI: 0.284–1.590, p = 0.366). Conclusions: Gender differences in spironolactone outcomes were observed; females might achieve more benefits than males in terms of HF and all-cause hospitalizations. These findings underscore the need for gender-sensitive management strategies in HFrEF treatment, particularly to address higher hospitalization risks in males.